O modelo ZFM: uma análise socioeconômica da capital Manaus no período 2011-2021 - Costa, Luiz Mateus dos Santos (Brasil, 2025)
This study analyzed the socioeconomic impacts of the Manaus Free Trade Zone (ZFM) on the capital of Amazonas from 2011 to 2021. Created in 1967, the ZFM uses tax incentives to attract industries, promote economic growth, and improve social indicators. The research relied on data from sources such as SUFRAMA and IBGE, evaluating economic indicators (revenue of the Manaus Industrial Hub, GDP, and job creation) and social indicators (population growth and MHDI). The results show that the ZFM was essential for industrialization, job creation, and income growth in the region, as well as for improving human development. However, challenges such as dependency on tax incentives and lack of economic diversification persist. The study concludes that the ZFM is a strategic model for regional growth, but its long-term sustainability depends on investments in sectors such as bioeconomy and technology, supported by adaptive public policies.